Controls on the Cd-isotope composition of Upper Cretaceous (Cenomanian–Turonian) organic-rich mudrocks from south Texas (Eagle Ford Group). (15th October 2020) - Sweere, Tim C.; Dickson, Alexander J.; Jenkyns, Hugh C.; Porcelli, Don; Ruhl, Micha; Murphy, Melissa J.; Idiz, Erdem; van den Boorn, Sander H.J.M.; Eldrett, James S.; Henderson, Gideon M.
Abstract: The isotopic composition of Cd buried in marine sediments may preserve valuable palaeoenvironmental information on past ocean redox conditions or biological cycling. It is unclear, however, how the Cd-isotope composition of the sedimentary record reflects these processes. In this study, new Cd-isotope data are presented, along with δ 13 C, and Cd, Mo and TOC concentrations, from organic-rich mudrocks from the southern Western Interior Seaway (WIS), spanning the Cenomanian–Turonian stages within the Eagle Ford Group of the Maverick Basin, Texas, USA. Relationships between [Cd/TOC], δ 114 Cd, and MoEF indicate that sedimentary Cd was derived from organic matter with additional contributions from CdS formed in euxinic water masses. Local redox conditions exerted a primary control on the δ 114 Cd composition of these deposits, with high δ 114 Cd values attributed to near-quantitative removal from seawater in euxinic environments. Lower δ 114 Cd values in non-euxinic environments may reflect isotopically light Cd associated with organic material due to partial remineralization. These observations imply that δ 114 Cd values of samples deposited in demonstrably euxinic conditions may be used to constrain the δ 114 Cdseawater coming into the Maverick Basin at this time and give a composition of 0.28 ± 0.11‰ (2 SD) for the Early Cenomanian. Samples from an interval of peak-organic carbon burial globally, namely Oceanic Anoxic Event 2 (OAE 2), show anomalous δ 114 Cd and [Cd] patterns compared to the rest of the data, implying a perturbation to the dissolved Cd pool. The data presented in this study demonstrate that sedimentary Cd isotopes preserve valuable information on the extent of Cd burial into sulfide-bearing sediments at both local and global scales.